Synthesis of structurally well-defined and liquid-phase-processable graphene nanoribbons - Narita, Akimitsu; Feng, Xinliang; Hernandez, Yenny; Jensen, Soren A.; Bonn, Mischa; Yang, Huafeng; Verzhbitskiy, Ivan A.; Casiraghi, Cinzia; Hansen, Michael Ryan; Koch, Amelie H. R.; Fytas, George; Ivasenko, Oleksandr; et al. (Nature Chemistry, 2014)
The properties of graphene nanoribbons (GNRs) make them good candidates for next-generation electronic materials. Whereas 'top-down' methods, such as the lithographical patterning of graphene and the unzipping of carbon nanotubes, give mixtures of different GNRs, structurally well-defined GNRs can be made using a 'bottom-up' organic synthesis approach through solution-mediated or surface-assisted cyclodehydrogenation reactions. Specifically, non-planar polyphenylene precursors were first 'built up' from small molecules, and then 'graphitized' and 'planarized' to yield GNRs. However, fabrication of processable and longitudinally well-extended GNRs has remained a major challenge. Here we report a bottom-up solution synthesis of long (>200 nm) liquid-phase-processable GNRs with a well-defined structure and a large optical bandgap of 1.88 eV. Self-assembled monolayers of GNRs can be observed by scanning probe microscopy, and non-contact time-resolved terahertz conductivity measurements reveal excellent charge-carrier mobility within individual GNRs. Such structurally well-defined GNRs may prove useful for fundamental studies of graphene nanostructures, as well as the development of GNR-based nanoelectronics. © 2014 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20